Elloset dearvan giellamet. Sámegiella nubbigiella oahpahus joatkkaskuvllas - Gaup, Inger Anne (UiT Norges arktiske universitet, 2015)
Abstract This master thesis is about education in second language Sami. My research is done in schools based in a city outside of Sami language administrative area. In the research, both students and teachers in the Northern Sami postgraduate studies have evaluated the different aspects of the education. Students in this research belong to different studies, and they represent all the different levels of language competence. Aside from the Sami second language subject, the students follow the school's regular education. The school offers Sami second language as an extra, optional subject in addition to their overall education. The teachers in this research mostly work with Sami tuition, in some schools, there is only one Sami teacher, while some schools have a few Sami teachers. How the school organizes language education is central to this job. The theoretical approach in this thesis is the frameworks theory, Language education and identity theory. By qualitative interviewing, I have gathered the data in this thesis. The empirical data is interpreted in the framework of theories. The data varies a great deal but also has many similarities between the different schools’ language education. The informants talk about missing parts in teaching. A person`s competence in Sami language has great significance for the person`s Sami identity. The teachers experience their work situation as hard in many ways, especially those who are the only employee at a school to work with the Sami education.